Noise-induced hippocampal damage: potential mechanisms - Molina, Sonia Jazmín (2021)
Exposure to noise of high intensities (>80 dB) is considered a stressful event and might produce both auditory and extra-auditory damage, including different central nervous system (CNS) injuries. Within the CNS, the hippocampus (HC), a structure related to several cognitive functions, has shown to be particularly susceptible to the effects of noise. Human and animal studies have demonstrated that exposure to noise can generate different HC-related alterations, including morphological, functional and behavioral changes (Molina et al. 2016b, 2019; Nadhimi and Llano 2020). Unfortunately, little is known about the mechanisms involved in noise-induced hippocampal damage and more research is needed to understand how the different alterations are caused. In addition, considering that noise exposure constitutes a public health problem that is increasing in urbanized societies, accurate knowledge of these mechanisms has clinical relevance as it can lead to develop preventive strategies. In this perspective, the possible mechanisms involved in noise-induced hippocampal cell damage will be discussed, as well as the pathways through which these mechanisms could be triggered by noise exposure.